Dynamic Mechanical Properties and Failure Mode of Artificial Frozen Silty Clay Subject to One-Dimensional Coupled Static and Dynamic Loads - Yuan, Pu; Yao, Zhao-ming; Ma, Qin-yong; Ma, Dong-dong; Zhang, Rong-rong (Advances in Civil Engineering, 2019)
The dynamic stress-strain relationship of artificial frozen silty clay under one-dimensional coupled static and dynamic loads is obtained using modified split Hopkinson pressure bar (SHPB) equipment. The variation in dynamic compressive strength, dynamic deformation modulus, energy dissipation, and failure mode of artificial frozen silty clay with axial precompressive stress ratio are studied in this research. Experimental results indicate that the dynamic stress-strain curves under uniaxial state and one-dimensional coupled static and dynamic loads can be divided into four stages, i.e., compaction stage, elastic stage, plastic stage, and failure stage. The dynamic compressive strength, first-stage deformation modulus, second-stage deformation modulus, and absorbed energy density of artificial frozen silty clay present a trend of first increase and then decrease with the increase of axial compressive stress ratio, and the axial compressive stress ratio corresponding to the peak value is 0.7 in this test. In addition, there is a very similar effect of axial precompressive stress ratio on dynamic compressive strength and second-stage deformation modulus of artificial frozen silty clay. At 0.4 axial compressive stress ratio, spall phenomenon appears at circumferential direction and center position of the frozen soil specimen has no obvious failure. Shear failure appears at 0.7 to 0.9 axial compressive stress ratio, and the larger the axial compressive stress ratio applies, the more obvious the shearing surface appears; moreover, comminution failure mode appears at 1.0 axial compressive stress ratio.